Towards our better future : (seize the opportunities) - Ramos, Fidel V. ([Manila, Philippines] : Ramos Peace and Development Foundation, Inc., 2012)
"We live in a rapidly evolving era - one that is experiencing dramatic transformation. For the Philippines -- as with our developing neighbors - severe poverty, economic decline, global warming/ climate change, rapid population growth, international terrorism, violent conflicts/ insurgencies and endemic diseases are just some of the problems shaping our world today. Most of these threats do not recognize national borders. They affect Filipinos directly and harshly, and impact deeply on the ways we think and live
Towards a more creative and responsive leadership -- Towards more responsible citizens -- Towards healthier, greener and more sustainable practices -- Towards a stronger cooperation -- Anecdotes
Includes index.
Keywords: SPEECHES, ADDRESSES, ETC